In search of authenticity : from Kierkegaard to Camus - Golomb, Jacob (Problems of modern European thought, 1995)
Great philosophers such as Kierkegaard, Nietzsche and Sartre have clearly been preoccupied by the possibility of authenticity. In this study, Jacob Golomb looks closely at the literature and writings of these philosophers in his analysis of their ethics.